The sacrificial son of Ibrahim: discourse on Q.37:102 with emphasis on Hamka’s Tafsir Azhar - Fadzil, Ammar (Indiana Publication, 2025)
This study investigates the identity of the sacrificial son mentioned in the Qur’anic narrative of Ibrahim, with particular focus on verse Q.37:102. It examines the exegetical discourse surrounding this passage by engaging with interpretations from classical scholars such as al-Tabari and Ibn Kathir, alongside the modern perspective of Hamka in his Tafsir Azhar. Through qualitative analysis of scriptural references, exegetical arguments, and historical contexts, the paper highlights the complexity of this narrative and its theological significance within Islamic thought. Special emphasis is placed on Hamka’s approach, which combines rigorous textual analysis with cultural insight, offering a distinctive resolution to the longstanding debate. The findings underscore the importance of careful engagement with primary sources and demonstrate Hamka’s extensive scholarship, ultimately affirming the identification of Ismail as the sacrificial son.